2021
DOI: 10.1021/acssuschemeng.1c01590
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Engineered Fe Single-Atom Electrocatalyst Based on Waste Pig Blood for High-Performance AEMFCs

Abstract: Biomass is the ideal precursor for fabricating oxygen reduction reaction (ORR) electrocatalysts due to its large-scale and low-cost production, as well as its renewability. Among various forms of biomass, especially waste pig blood is a sustainable precursor for the synthesis of functional electrocatalysts. However, various proteins or metal substances present in the waste pig blood act as impurities and impede the electrocatalytic performance, preventing its direct use as an electrocatalyst. Herein, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The N 1s core-level spectra of p-CoSi 1 N 3 @D is well divided into four peaks, including pyridinic N, CoN, pyrrolic N, and graphitic N (Figure S12, Supporting Information). [45][46][47][48][49][50] The pyrrolic N in binding energy of 400.0 eV served as the dominant chemical species. Most importantly, different from diatomite, only a weak peak located at 101 eV, which associated to the SiC bond, can be observed in the high-resolution Si 2p XPS spectra of p-CoSi 1 N 3 @D (Figure S13, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The N 1s core-level spectra of p-CoSi 1 N 3 @D is well divided into four peaks, including pyridinic N, CoN, pyrrolic N, and graphitic N (Figure S12, Supporting Information). [45][46][47][48][49][50] The pyrrolic N in binding energy of 400.0 eV served as the dominant chemical species. Most importantly, different from diatomite, only a weak peak located at 101 eV, which associated to the SiC bond, can be observed in the high-resolution Si 2p XPS spectra of p-CoSi 1 N 3 @D (Figure S13, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In the AEMFC conditions with PBC/900/M catalyst on the cathode, P max of 658 mW cm À 2 was reached, but more importantly the fuel cell showed excellent stability with current loss of ca 16 % after 100 h of constant operation. [163] This shows that highly active and stable SACs can also be prepared from waste materials using a rather simple synthesis route.…”
Section: Iron-based Sacs For Aemfc Cathodementioning
confidence: 96%
“…Most commonly used methods for producing SACs rely on the usage of sacrificial metal to prevent agglomeration of metal species, e. g. Zn in ZIF-8. In contrast to the usual careful building of SACs, Lee et al [163] synthesised Fe-SACs using waste material, namely iron-rich pig blood, as a precursor for FeÀ N x active sites and combined it with thermally exfoliated graphene oxide using short heat-treatment under NH 3 conditions. The bestperforming material (PBC/900/M catalyst) contained 1.5 wt% iron, which was well distributed as atomically dispersed sites as per STEM study (Figure 13a) and further analysis with XAS indicated that Fe was coordinated with nitrogen atoms (Figure 13b) with a coordination number of 4.…”
Section: Iron-based Sacs For Aemfc Cathodementioning
confidence: 99%
“…[72][73][74] Biomass resources include all living organisms (animal, plant and microorganism) and their subsidiary products. Biomass resources from animal and microorganism include feather, shell, cell or metabolic waste, whose main components are protein, [75][76][77] lipid [78] and mineral. [79][80][81][82] Biomass resources of plant include fruit, leave and flower, whose main components are cellulose, [83][84][85] pectin [86][87][88][89] and lignin.…”
Section: Biomass-derived Carbon-based Micsmentioning
confidence: 99%